Independent and additive effects of cytokine patterns and the metabolic syndrome on arterial aging in the SardiNIA Study - Scuteri, Angelo; Orru, Marco; Morrell, Christopher; Piras, Maria Grazia; Taub, Dennis; Schlessinger, David; Uda, Manuela; Lakatta, Edward G. (Atherosclerosis, 2011)
Metabolic syndrome (MetS) and its components accelerate age-associated increases in arterial stiffness and thickness. We investigated whether specific proinflammatory cytokines contribute to arterial aging, independent of age, sex, MetS, and other traditional CV risk factors. MetS components (ATP III criteria) and arterial properties were assessed in 6148 subjects, aged 14–102 in Sardinia, Italy. Common carotid artery (CCA) diameter, intima-media thickness (IMT), and aortic pulse wave velocity (PWV), adiponectin, leptin, high-sensitivity C reactive protein (hsCRP), monocyte chemoattractant protein 1 (MCP1), and interleukin 6 (IL6) were measured. While cytokine levels – except for MCP1 – were significantly higher (lower for adiponectin) in MetS than in control subjects, and the increased PWV and CCA IMT with aging were associated with MetS, this association was independent of cytokine levels (p<0.001 for both PWV and CCA IMT). Specific cytokines, however, were significantly associated with arterial stiffness (higher leptin, p<0.001, and higher hsCRP, p<0.001) or thickness (lower adiponectin, p<0.05, and higher IL6, p<0.001) – independent of age, sex, MetS and other traditional CV risk factors. The co-occurrence of both MetS and higher cytokines levels was associated with greater increases in arterial stiffness and thickness. While MetS and specific cytokine patterns associated with arterial aging, the increases in arterial stiffness and thickness are greater when both MetS and higher cytokine levels are present, suggesting a possible synergistic effect of MetS and inflammation on the arterial wall.